Rootstocks for Cherries from the Department of Fruit Science Budapest - Hrotkó, K.; Magyar, L. (International Journal of Horticultural Science, 2004)
Cherry rootstock breeding started at the Department of Fruit Science, SSU Budapest by the late 50-s and the activity can be divided into three main groups. In the first stage the activity was focused on collection of native mahaleb cherry (Prunus mahaleb L.) varieties lead by L. Sebők. After evaluation in the nursery and orchard tests there are four promising rootstock cultivars selected from this material: ’Korponay’ used as self fertile seed tree, its seedlings are recommended for sour cherries. The mahaleb varieties ’Bogdány’ (vigorous), ’Egervár’ and ’Magyar’ (medium vigour) are propagated by cuttings. The next project has started in 1979 with the aim to select self fertile mahaleb seed trees producing homogeneous seedling populations with reduced vigour. Inbred populations from isolated flowering self fertile trees were produced and planted out in 1980. The inbreeding of ’Korponay’ self fertile P. mahaleb variety resulted in specimens with different fruit colour (yellow, red, black), fruit shape and size. From among them self fertile trees were selected with various growth characteristics. Seedlings of that self fertile mother trees (S2 population) were tested in seedbed, they showed homogeneous phenotype characteristics as liners in the nursery. As rootstock of ’Érdi bőtermő’ sour cherry in the orchard most of the S2 lines proved to be less vigorous in comparison to SI popuplations. ’Érdi bőtermő’ trees budded on certain S2 lines in the orchard are more productive than those on S1 (’Korponay’ seedling). Characteristics of the S2 generation as seed tree were studied as well. We expect to get morphologically homogeneous seedling populations with different growth vigour and good productivity in the later inbred generations. In the last couple of decades the research activity concerning ground-cherry and its hybrids resulted in dwarfing rootstocks. Prunus fruticosa Pall. hybrids from the natural flora of Hungary were collected and artificial hybrids were created between P. fruticosa and mahaleb cherry. Most of them are in the initial tests, only one of them is before registration, named ’Prob’, which is a dwarf rootstock for sweet cherry. By the screening of new hybrids medium vigorous or semi dwarfing and precocious rootstocks seem to be promising for the cherry industry.